A Review of Comparison of Complications of Vaginal Hysterectomy with and without Concomitant Surgery for SUI: A 5 Years' Experience at a Tertiary Care Hospital of Pakistan - Raheela Mohsin Rizvi; Munnazza Akhtar; Nadeem Faiyaz Zuberi (Hindawi Limited, 2013)
Objective. The study was performed to review the complications of surgery for POP with or without surgery for SUI. This included the need for second procedure two years after the primary surgery. Study Design. We conducted a retrospective cross-sectional comparative study at the Aga Khan University, Karachi, Pakistan. International Classification of Diseases, 9th revision, Clinical Modification (ICD-9-CM) was used to identify women who underwent vaginal hysterectomy with anterior/posterior repair alone and those with concomitant tension-free vaginal tape surgery for urodynamic stress incontinence. Results. The 28 cases of VH/repair combined with TVT were compared for complications with 430 cases of VH with repair alone. The basic characteristics like age, BMI, and degree of prolapse showed no statistical difference among two groups. The main comorbidities in both groups were hypertension, diabetes, and bronchial asthma. We observed no significant differences in intraoperative and postoperative complications except for cuff abscess, need for medical intervention, and readmission following discharge from hospital, which were higher in cases with vaginal hysterectomy with concomitant TVT. Conclusions. Vaginal hysterectomy is an efficient treatment for uterovaginal prolapse with a swift recovery, short length of hospital stay, and rare serious complications. The addition of surgery for USI does not appear to increase the morbidity.